Formulation and evaluation of crispy chicken burger patty - Nazirah Mohd Rosli
Deep-fried battered products are very appealing nowadays since they are both appetizing and palatable. The development of crispy chicken burger paffies made from chicken patties has never been conducted before because it is complicated to achieve the desirable properties. Thus, in collaboration with Juara Rasa Maju Sdn. Bhd., this study was aimed to formulate a batter system for crispy chicken burger patties using wheat flour-based batter and rice flour-based batter with the ratios of 2:2:1:1 and 2:1:2:1 (wheat flour/rice flour: corn flour: crispy flour: spicy flour). The ratios were suggested by Juara Rasa Maju Sdn. Bhd. The developed crispy chicken burger patties were evaluated in terms of their proximate compositions which include moisture, ash, fat, protein, and carbohydrate contents. Then, the crispy chicken burger patties made from rice flour-based batter with a formula ratio of 2:2:1:L (RFBBI) exhibited the lowest moisture and fat compositions but the highest protein composition. The evaluation of sensory properties in terms of overall acceptability, appearance, taste, crispness, juiciness, and colour revealed that RFBB1 exhibited the best acceptability scores for all attributes than other formulations. The storage qualities of crispy chicken patties packed using different types of packaging (Low-Density Polyethylene (LDPE), Medium-Density Polyethylene (MDPE), and High-Density Polyethylene (HDPE), and stored at different temperatures (- 18,4, and 25° C) for 12 days was investigated in terms of colour and texture. For all types of packaging, the hardness of crispy chicken burger paffies decreased over time when stored at different storage times. Regardless of the types of packaging, crispness increased significantly throughout the storage time for the samples kept at cold and frozen temperatures. These textural changes were due to the moisture content as supported by literature reviews. The low in hardness and high in crispness value helps in providing crispier products that are not too hard and dry which is needed in this study. The crispy chicken burger patties exhibited a decrease in lightness (L* value) and an increase in yellowness (b* value) throughout the storage time. The desired colour for crispy chicken burger patties after the storage was higher L* and highest b* which produced light golden brown colour. In conclusion, crispy chicken burger patties produced using rice flour-based batter of ratio 2:2:1:1 was the most acceptable formulation and LDPE packaging material at either cold or frozen temperature is the suitable packaging material and storage temperature, respectively to store the crispy chicken burger patties produced in this study.